Crisis in the era of the end of cheap food: capitalism, cannibalism, and racial anxieties in Soylent Green. (20th October 2019) - Yates, Michelle
ABSTRACT: Not just a reductionist representation of overpopulation, Soylent Green offers a nuanced critique of capitalism. In the course of the film, audiences learn that the seaplankton of which soylent green is supposedly composed no longerexists. The audience is horrified to discover by the end of the film that "soylent green is people." While seemingly horrific, the notion of humans cannibalizing themselves in order to survive functions metaphorically for the system of capitalism, where human lives are cannibalized, wasted at ever accelerating rates in order to procure the most profit possible. In this respect, Soylent Green offers avisual representation of what Jason Moore calls the end of cheapfood. Yet, even as Soylent Green offers a powerful representation of capitalism's crisis state in the era of the end of cheap food, the film asks audiences to re-invest in hegemonic white masculinity, a system of power and oppression intimately linked to capitalism. In particular, the film embodies what Hamilton Carroll writes about as white male injury, a new form of white masculine identity politics. Even as the film offers up a powerful critique of capitalism's crisis state, it simultaneously does so through reproducing a discourse of white male injury.